Big Data Analytics for Industrial Parks Management in the Sultanate of Oman: Challenges and Opportunities Future Research - Alyahmadi, Dhiyab Musabah; Kasim, Hairoladenan; Ramli, Rohaini Binti (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The integration of Big Data Analytics became pivotal in addressing the complex challenges associated with industrial park management. This research explores the transformative potential of Big Data Analytics in the management of industrial parks within the Sultanate of Oman, laying the groundwork for future research endeavors. The article delves into the current state of industrial parks in Oman, highlighting existing challenges and the nascent landscape of Big Data Analytics adoption for a government agency called (Madayn). Through an exploration of real-world case studies, the article underscores the diverse applications of Big Data Analytics, ranging from predictive maintenance to supply chain optimization. This research will Identify key challenges firstly, data challenges (data collection, data processing, data storage and data analysis and modelling), and secondly, management challenges, (governance, Lack of people skills and investment costs). A qualitative methodology will be adopted and a single case study will be conducted in the Sultanate of Oman (Madayn). The article will propose a gap solution to pave the way for successful implementation. Also, it to pave the for researchers to investigate this crucial domain. The importance of strategic planning, investment in data infrastructure, and collaborative partnerships with technology providers are emphasized as crucial elements in the effective adoption of Big Data Analytics. Finally, the article outlines a vision for future research endeavors in the domain of Big Data Analytics for industrial park management in Oman. It calls for a more in-depth exploration of specific applications, the development of tailored training programs, and the examination of the long-term socio-economic impact of Big Data adoption. By fostering a culture of innovation and research collaboration, Oman can position itself as a trailblazer in the intersection of industrial management and cutting-edge data analytics, shaping a resilient and visionary future for its industrial landscape.